Creation of a eukaryotic multiplexed site-specific inversion system and its application for metabolic engineering - Jieyi Li; Simiao Gong; Yuan Ma; Peiyan Han; Nan Wang; Zongheng Fu; Xinyi Zhang; Xinyang Huang; Tianyu Yang; Hanze Tong; Guang-Rong Zhao; Yi Wu; et al. (Nature Communications)
Abstract The site-specific recombination system is a versatile tool in genome engineering, enabling controlled DNA inversion or deletion at specific sites to generate genetic diversity. The multiplexed inversion system, which preferentially facilitates inversion at reverse-oriented sites rather than deletion at same-oriented sites, has not been found in eukaryotes. Here, we establish a multiplexed site-specific inversion system, Rci51-5/multi-sfxa101, in yeast. Firstly, we develop a high-throughput screening system based on the on/off transcriptional control of multiple markers by DNA inversion. After two rounds of progressively stringent directed evolution, a mutant Rci51-5 shows an ability of multisite inversion and a ~ 1000-fold increase in total inversion efficiency against the wild-type Rci derived from Salmonella typhimurium. Subsequently, we demonstrate that the Rci51-5/multi-sfxa101 system exhibits significantly lower deletion rate than the Cre/multi-loxP system. Using the synthetic metabolic pathway of β-carotene as an example, we illustrate that the system can effectively facilitate promoter substitution in the metabolic pathway, resulting in a more than 7-fold increase in the yield of β-carotene. In summary, we develop a multiplexed site-specific inversion system in eukaryotes, providing an approach to metabolic engineering and a tool for eukaryotic genome manipulation.